Anti-inflammatory potential of a carvedilol gel in the pulpal tissue of rats after dental bleaching: A histopathological evaluation - Louzada, Lidiane M. [UNESP]; Briso, André L F [UNESP]; Benetti, Francine [UNESP]; Vieira, Letícia B [UNESP]; de Castilho Jacinto, Rogério [UNESP]; Dezan-Júnior, Elói [UNESP]; Cintra, Luciano T A [UNESP] (Wiley, 2019)
AIM: Carvedilol is an antioxidant that decreases inflammation in periodontitis. The hydrogen peroxide (H2 O2 ) of bleaching gel causes inflammation and necrosis of the dental pulp. In the present study, we evaluated the anti-inflammatory potential of carvedilol in the pulp of rats after bleaching. METHODS: The right upper molars of rats received 35% H2 O2 (1× 30 minutes), and the left upper molars were used as the control. Half of the rats received carvedilol gel (1× 10 minutes), forming the following groups: bleached, bleached followed by carvedilol (bleached+carvedilol), and control. After 2 and 30 days (N = 7 hemi-maxillae/group), the rats were killed for histological evaluation, and statistical tests were performed (P < 0.05). RESULTS: After 2 days, the bleached group showed necrosis in the occlusal third of the coronal pulp, and in the bleached+carvedilol group, severe inflammation (P > 0.05), both different from the control (P < 0.05). In the middle third, the bleached group showed severe inflammation, and the bleached+carvedilol group showed moderate inflammation (P > 0.05), with the only difference between the bleached and control groups (P < 0.05). In the cervical third, the bleached group showed moderate inflammation, and the bleached+carvedilol group showed mild inflammation (P > 0.05). The difference again was only between the bleached and control groups (P < 0.05). At 30 days, there was no inflammation and a marked amount of tertiary dentin in bleached teeth (P > 0.05). CONCLUSION: Carvedilol gel has the potential of minimizing H2 O2 damage, especially in deep regions of the dental pulp of rats after bleaching.
Keywords: carvedilol; hydrogen peroxide; inflammation; pulp; tooth bleaching